“La historia que nos ha sido arrebatada”: crisis de representación de la memoria y la historia en Entrada libre de Carlos Monsiváis - Ramírez Méndez, Alejandro (Romanica Silesiana, 2023)
In Entrada libre (1987), Carlos Monsiváis, ruminates about the importance of civil resistance in Mexico after decades of political instability, corruption, and violence. The cruel actions of the ‘dirty war’ left an unstable democratic system and an absent-minded population, which was still trying to understand the violent repression against left-wing groups. Under these conditions, Monsiváis questions the role of civil society in the production of mechanisms of resistance and reconciliation against a large history of abusive treatments and misuses that generated crisis in the country. This essay rethinks the representation of memory and history in the chronicles of Carlos Monsiváis. This project analyzes how the depiction of an the everyday life becomes an alternative method of expression for the a society in resistance, as well as a reevaluation of the meaning behind “historia nacional” and memory as the foundation of the perspective of time in Mexican society.